Pengaruh Keterampilan Berpikir Kritis dan Motivasi Berprestasi Terhadap Hasil Belajar Fisika Peserta Didik di SMA Negeri 2 Gowa - Sidin Ali; Muhammad Arsyad; Syamsinar Syamsinar (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a survey study that aims to understand the overview of students' critical thinking skills, achievement motivation, and physics learning outcomes, and then to analyze the direct and indirect effects of several variables. Sampling is done using a multiple-stage random sampling technique, assuming that all classes are relatively homogeneous, resulting in a sample size of 80 students from SMA Negeri 2 Gowa. The data is obtained through critical thinking skill test instruments, achievement motivation questionnaires, and physics learning outcome tests. The collected data will be processed using two types of analysis techniques, namely descriptive analysis, and inferential analysis, using path analysis. The descriptive analysis concludes that students' critical thinking skills, achievement motivation, and physics learning outcomes are all in the high category. Additionally, the inferential analysis concludes that: critical thinking skills have a direct and significant positive effect on physics learning outcomes of students, critical thinking skills have a direct and significant positive effect on achievement motivation of students, achievement motivation has a direct and significant positive effect on physics learning outcomes of students, and critical thinking skills have an indirect and significant positive effect on physics learning outcomes through achievement motivation of students